أساليب تنفيذ العقوبة داخل المؤسسات العقابية في الجزائر - شينة, علي (University of Eloued جامعة الوادي, 2020)
تعد المؤسسات العقابية بمثابة مؤسسات تقيمها الدولة من أجل استقبال المحكوم عليهم بعقوبات مقيدة لحريتهم يقضون فيها عقوبتهم كالحبس والسجن والاعتقال وغيرها , غير أن هذه المؤسسات تختلف باختلاف العقوبة وكذلك باختلاف المحكوم عليهم بتلك العقوبة , كما يختلف نظام العمل بها وأساليب المعاملة للمحكوم عليه وذلك كله من أجل التخفيف من الجرائم من جهة وإعادة إدماج المحكوم عليهم من جهة ثانية .Punitive institutions are considered to be institutions established by the state in order to receive those convicted of penalties that restrict their freedom in which they spend their sentences such as imprisonment, imprisonment, detention, and others. However, these institutions differ according to the different punishment, as well as the difference in those who are condemned to that punishment, as well as the system of work in them and the methods of treatment for the convicted person, all for the sake of Mitigation of crimes on the one hand, and the reintegration of convicts on the other
قال
Keywords: المؤسسات العقابية اساليب تنفيذ العق ; بة